Tourniquet-applied upper limb orthopaedic surgery results in increased inflammation and changes to leukocyte, coagulation and endothelial markers. - Stephen F Hughes; Beverly D Hendricks; David R Edwards; Jim F Middleton (PLoS ONE)
Purpose During this pilot clinical study, patients scheduled for elective tourniquet-applied upper limb orthopaedic surgery were recruited to investigate the effects of surgery on various biological markers (n = 10 patients). Methods Three venous blood samples were collected from the arm at the ante-cubital fossa, at baseline (pre-operatively), 5 and 15 minutes after reperfusion (post-operatively). Neutrophil and monocyte leukocyte sub-populations were isolated by density gradient centrifugation techniques. Leukocyte activation was investigated by measuring the cell surface expression of CD62L (L-selectin), CD11b (Mac-1) and the intracellular production of hydrogen peroxide (H2O2), via flow cytometry. C-reactive protein (CRP) was measured using a clinical chemistry analyser. Plasma concentrations of protein C and von Willebrand factor (vWF) were measured using enzyme-linked fluorescent assays (ELFA). Results Following tourniquet-applied upper limb orthopaedic surgery, there was a decrease in neutrophil CD62L expression (p = 0.001), an increase in CD11b expression and in the intracellular production of H2O2 by neutrophils and monocytes (p<0.05). An increase in CRP concentration (p<0.001), a decrease in protein C concentration (p = 0.004), with a trend towards elevated vWF levels (p = 0.232) were also observed during this time. Conclusions Conventionally, patients undergoing orthopaedic surgery have been monitored in the peri-operative period by means of CRP, which is a non-specific marker of inflammation. This test cannot differentiate between inflammation due to current or pre-existing disease processes and the development of ischaemia-reperfusion injury surgery. The findings from this study suggest that markers such as CD11b, protein C and H2O2 may provide alternative ways of assessing leukocyte and coagulation activation peri-operatively. It is proposed that by allowing orthopaedic surgeons access to laboratory markers such as CD11b, protein C and H2O2, an accurate assessment of the extent of inflammation due to surgery per se could be made.